The US Health System An Assessment and Prospective Directions for Reform - Docteur, Elizabeth (OECD Economics Department Working Papers, 2003)
This paper assesses the performance of the United States health system in an international context and discusses potential directions for reform. The US health system is unique among OECD countries in its heavy reliance on the private sector for both financing and delivery of health care. The public sector plays a not-insignificant role, providing coverage for the elderly, disabled and poor, and spending as much on health as a share of GDP as is spent in total by many OECD countries. The system is considered highly flexible, capable of evolving quickly to address the changing preferences of consumers and the incentives put in place by the requirements of payers and government regulation. It is also characterised by excellent access by the insured population to the latest advances in medical technology. However, 14 per cent of Americans lack insurance coverage, and the decentralised, multi-payer approach to financing and regulation provides relatively few levers to control ...